Information Technology Adoption Model in the Auditing Profession with a Sustainable Development Approach - ALQURAISHI, MOHAMMED A.ALHASAN MOHAMMED; Banitalebi Dehkordi, Bahareh; RAZOOQI ABBAS, SIRAJ; Yazdanian, Mansour (Business, Marketing, and Finance Open, 2026)
This study aims to develop a model for information technology (IT) adoption in the auditing profession, aligned with the principles of sustainable development. The study was conducted over a six-month period, from March to August 2025, to ensure a comprehensive data collection and analysis process. A mixed-methods approach was employed, combining qualitative interviews with quantitative analysis. In the first phase, semi-structured interviews were conducted with 12 auditing experts and analyzed through thematic coding, resulting in the identification of 77 key indicators. These indicators were refined using the fuzzy Delphi method, confirming expert consensus. A structured questionnaire was then developed based on the finalized indicators and distributed among auditors in publicly listed companies. Structural equation modeling (SEM) using Smart PLS was applied to validate the model. The results identified 12 core dimensions influencing IT adoption in auditing: Big Data, Analysis and Prediction, Software Utility, Specialized Human Resources, Data Security, Environmental Considerations, Improved Efficiency, Enhanced Analytical Depth, Better Decision Making, Enhanced Auditor Reputation, Reduced Risk of Human Error, and Audit Reporting Quality. While the study does not directly measure sustainability outcomes, the identified IT-driven improvements reflect a broader conceptual alignment with sustainable development goals—particularly in terms of enhancing transparency, accountability, and operational efficiency. Future research is recommended to empirically examine the long-term sustainability impacts of IT adoption in auditing.It can be concluded that adopting integrated reporting, using technology, and actively engaging with stakeholders can increase auditors' effectiveness in promoting sustainable development.